Relationships Between Perivascular Adipose Tissue and Abdominal Aortic Aneurysms - Ye, Tongtong; Zhang, Guangdong; Liu, Hangyu; Shi, Junfeng; Qiu, Hongyan; Liu, Yongping; Han, Fang; Hou, Ningning (Frontiers in Endocrinology, 2021)
Abdominal aortic aneurysms (AAAs) are typically asymptomatic, and there is a high mortality rate associated with aneurysm rupture. AAA pathogenesis involves extracellular matrix degradation, vascular smooth muscle cell phenotype switching, inflammation, and oxidative stress. There is increasing evidence of excessive adipocyte accumulation in ruptured AAA walls. These excessive numbers of adipocytes in the vascular wall have been closely linked with AAA progression. Perivascular adipose tissue (PVAT), a unique type of adipose tissue, can be involved in adipocyte accumulation in the AAA wall. PVAT produces various chemokines and adipocytokines around vessels to maintain vascular homeostasis through paracrine and autocrine mechanisms in normal physiological conditions. Nevertheless, PVAT loses its normal function and promotes the progression of vascular diseases in pathological conditions. There is evidence of significantly reduced AAA diameter in vessel walls of removed PVAT. There is a need to highlight the critical roles of cytokines, cells, and microRNA derived from PVAT in the regulation of AAA development. PVAT may constitute an important therapeutic target for the prevention and treatment of AAAs. In this review, we discuss the relationship between PVAT and AAA development; we also highlight the potential for PVAT-derived factors to serve as a therapeutic target in the treatment of AAAs.